If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 9 = 7x + 3 Reorder the terms: 9 + 11x = 7x + 3 Reorder the terms: 9 + 11x = 3 + 7x Solving 9 + 11x = 3 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 9 + 11x + -7x = 3 + 7x + -7x Combine like terms: 11x + -7x = 4x 9 + 4x = 3 + 7x + -7x Combine like terms: 7x + -7x = 0 9 + 4x = 3 + 0 9 + 4x = 3 Add '-9' to each side of the equation. 9 + -9 + 4x = 3 + -9 Combine like terms: 9 + -9 = 0 0 + 4x = 3 + -9 4x = 3 + -9 Combine like terms: 3 + -9 = -6 4x = -6 Divide each side by '4'. x = -1.5 Simplifying x = -1.5
| 81=5y+11 | | 2x=24 | | 16-4m=28 | | -3x+7-2x=4x-2 | | 5(x-3)=3(x+3) | | 3x+9=63 | | 2x-1=x+3 | | -2v-1=-7 | | 19+z=36 | | 16x=13x+x+14 | | x-4=-6x+5+5x-1 | | -3x-10=5x+6 | | 8-5y=12 | | 4k-3=1 | | 25c+55c=c | | 2(x-3)=x-5 | | u+5=8 | | a=0.5bh | | 5768734x+67=6478-56x | | 3(x-5)=2(2x-1) | | 5x-8=4x | | -7(x+2)+10=-(-x+6) | | 2(3x-5)=20 | | 6x+21=2x+117 | | 12x-36+2x=-4-2x | | 2-4x=30 | | 2(x-2)=-5(3-x)-1 | | 5(x-2)-(7x-12)=x+1 | | 139-2x=34x+15 | | 8x-(6x-1)=2 | | x-2-5=11 | | 3(2x-1)=4x-5 |